Sugar-based amphiphilic nanoparticles arrest atherosclerosis in vivo - Lewis, Daniel R; Petersen, Latrisha K; York, Adam W; Zablocki, Kyle R; Joseph, Laurie B; Kholodovych, Vladyslav; Prud'homme, Robert K; Uhrich, Kathryn E; Moghe, Prabhas V (Proceedings of the National Academy of Sciences - PNAS, 2015)
Atherosclerosis, the build-up of occlusive, lipid-rich plaques in arterial walls, is a focal trigger of chronic coronary, intracranial, and peripheral arterial diseases, which together account for the leading causes of death worldwide. Although the directed treatment of atherosclerotic plaques remains elusive, macrophages are a natural target for new interventions because they are recruited to lipid-rich lesions, actively internalize modified lipids, and convert to foam cells with diseased phenotypes. In this work, we present a nanomedicine platform to counteract plaque development based on two building blocks: first, at the single macrophage level, sugar-based amphiphilic macromolecules (AMs) were designed to competitively block oxidized lipid uptake via scavenger receptors on macrophages; second, for sustained lesion-level intervention, AMs were fabricated into serum-stable core/shell nanoparticles (NPs) to rapidly associate with plaques and inhibit disease progression in vivo. An AM library was designed and fabricated into NP compositions that showed high binding and down-regulation of both MSR1 and CD36 scavenger receptors, yielding minimal accumulation of oxidized lipids. When intravenously administered to a mouse model of cardiovascular disease, these AM NPs showed a pronounced increase in lesion association compared with the control nanoparticles, causing a significant reduction in neointimal hyperplasia, lipid burden, cholesterol clefts, and overall plaque occlusion. Thus, synthetic macromolecules configured as NPs are not only effectively mobilized to lipid-rich lesions but can also be deployed to counteract atheroinflammatory vascular diseases, highlighting the promise of nanomedicines for hyperlipidemic and metabolic syndromes.